What motivates tourism and hospitality employees to practice presenteeism?. (September 2022) - Knani, Mouna
Abstract: Presenteeism, attending work while ill, has an impact on organizations' productivity and employees' health. Despite it being widespread, this global phenomenon is understudied in the tourism and hospitality (hereafter T&H) sector. In this study, we intend to explore the motives for presenteeism by reporting on its associations with work-related and non-work-related (individual attitudes and sociodemographic indicators) factors. Data were collected online among 1394 employees in the T&H sector. All the scales used in this study are adapted from the literature. The results show that for work-related factors, presenteeism is positively related to job demand, work-related depression, anxiety, and irritation, but negatively related to decision latitude and social (supervisor and coworker) support, salary perceptions, promotion perceptions, and job satisfaction. Regarding individual attitudes, work engagement decreases presenteeism whereas organizational citizenship behavior does not affect presenteeism. The effects of demographic indicators on presenteeism are limited to gender and the number of children at home. This study is one of the few studies that examine the associations of presenteeism with work-related and non-work-related factors in T&H organizations. It highlights the relevance of the job demands-control and job demands-resources model in explaining presenteeism among T&H employees.